Does Religiosity Moderate Personal Tax Compliance? A Study Involving In-House Tax Professionals of Malaysian Businesses - Nivakan, Sritharan; Salawati, Sahari; Cheuk, Sharon Choy Sheung; Mohamed Ahmad, Syubaili (Ural Federal University, 2023)
This study limns the moderating impact of religiosity made on the in-house tax professionals who deal with tax affairs in the corporate sectors in Malaysia. Therefore, we intend to produce a seminal article, wherein religiosity is tested for its moderating effect between the determinants such as peers’ tax compliance, tax audit, service quality of tax authority, satisfaction with government spending, and the level of tax compliance among the tax affairs officers. Purposive and snowball sampling techniques have been chosen to collect data from the tax professionals of the Malaysian businesses. A total of 392 respondents have managed to participate in this survey questionnaire to disclose their opinion. “SmartPLS’ is used to analyse the data. The finding reveals that religiosity does not moderate the relationship between the determinants and the level of tax compliance among the Malaysian tax professionals. The interpretation of the relationship between the “Factors of Personal tax compliance’ (Independent variables) among the tax affairs officers of the Malaysian businesses and the “Personal tax compliance behaviour’ (Dependent variable) can be explained by 83.9 percent by the variance studied. To produce an extensive and expeditious report of exploration on the said nexus of personal tax compliance and the taxpayers’ decision on the corporate tax compliance, the selection of one type of data collection approach is not sufficient. Therefore, the future researchers are advised to make research with the collection of supplementary data, such as interviews, as their primary data collection so that the robustness of their findings could be strengthened.